Lateralization of facial emotion processing and facial mimicry - Blom, Stephanie S. A. H. (2019)
The two halves of the brain are believed to play different roles in emotional processing. In studies involving chimeric faces, emotional expressions in the left visual field are more strongly perceived as emotional than those in the right visual field. Notably, the role of facial mimicry has not been studied in relation to hemispheric lateralization. In the current study, which used a novel stimulus set of chimeric faces, we proposed and found that emotional intensity judgments replicate the left visual field bias for facial expressions of emotions. While a general facial mimicry effect to the chimeric faces occurred for the corrugator muscle, these mimicry effects were not related to the visual field bias. The results suggest that encoding the emotionality of another person's facial expression might occur independent from the mere mimicry of the facial expression itself.